DISTINCT FEATURES OF STAGHORN NEPHROLITHIASIS IN SOUTH OF RUSSIA - A. V. Кhasigov; M. A. Khagokov; I. I. Belousov; M. I. Kogan (Вестник урологии)
A study of staghorn nephrolithiasis pathogenesis with aim of stone prevention has particular importance. Knowledge of urine stones’ chemical structure is a basic in individual metaphylaxis. A complex biochemical analysis of blood and 24-hours urine for mineral disturbances detection in 136 patients with staghorn stones was performed. An x-ray analysis for detection a mineral structure of 130 stones was done. An analysis of chemical structure of stones and blood biochemical disturbances showed the typical changes of metabolism in specific stones only in 56,9% cases, which make an understanding of processes underlying stone formation more complicated.